Prevalence and Risk Factors of Inadequate Micronutrient Intake among Children Aged 6-23 Months in Indonesia - Nathasa Khalida Dalimunthe; Ikeu Ekayanti; Cesilia Meti Dwiriani (Universitas Airlangga, 2022)
Background: Poor quality and quantity are the main factors that contribute to the increasing inadequacy of micronutrients intake such as Iron, Calcium, Zinc, Vitamins A, and C since the complementary food was introduced at 6 months of infant’s age. Objectives: To analyze the prevalence and risk factors of inadequate micronutrients intake among children aged 6-23 months in Indonesia. Methods: A cross-sectional study used Individual Food Consumption Survey 2014 data from Indonesian Health Study and Development Agency involving 1575 children aged 6-23 months as the total subjects. Minimum Dietary Diversity (MDD) was measured by eight food groups for children under two years old. The prevalence of inadequate micronutrients intake used the probability approach. Binary logistic regression was used as a multivariate test to determine the risk factors of inadequate micronutrients intake. Results: The highest prevalence of inadequate micronutrients intake was vitamin C, while the lowest was zinc, with overall inadequate multiple micronutrients intake being 61.9%. About 57.7% and 15.9% of subjects were low in energy intake and achieved the MDD, respectively. Lived in rural area [OR=1.37(95%CI:1.06-1.77)], low education mother [OR=1.71(95%CI:1.32-2.22)], low energy intake [OR=6.22(95%CI:4.84-7.99)] and not achieved MDD [OR=4.84(95%CI:3.47-6.75)] were more likely to have inadequate micronutrients intake, while not consuming breast milk were less likely to have inadequate micronutrients intake in children [OR=0.55(95%CI:0.43-0.71)]. Conclusions: Almost two-thirds of subjects were inadequate in overall multiple micronutrients. Low energy intake and not achieved MDD were the highest risk of inadequate micronutrients intake of subjects, instead of low mother education and living in rural areas.